The determinants of dietary diversity and nutrition: ethnonutrition knowledge of local people in the East Usambara Mountains, Tanzania - Bronwen Powell; Rachel Bezner Kerr; Sera L. Young; Timothy Johns (BMC, 2017)
Abstract Background Diet and nutrition-related behaviours are embedded in cultural and environmental contexts: adoption of new knowledge depends on how easily it can be integrated into existing knowledge systems. As dietary diversity promotion becomes an increasingly common component of nutrition education, understanding local nutrition knowledge systems and local concepts about dietary diversity is essential to formulate efficient messages. Methods This paper draws on in-depth qualitative ethnographic research conducted in small-scale agricultural communities in Tanzania. Data were collected using interviews, focus group discussions and participant observation in the East Usambara Mountains, an area that is home primarily to the Shambaa and Bondei ethnic groups, but has a long history of ethnic diversity and ethnic intermixing. Results The data showed a high degree of consensus among participants who reported that dietary diversity is important because it maintains and enhances appetite across days, months and seasons. Local people reported that sufficient cash resources, agrobiodiversity, heterogeneity within the landscape, and livelihood diversity all supported their ability to consume a varied diet and achieve good nutritional status. Other variables affecting diet and dietary diversity included seasonality, household size, and gender. Conclusions The results suggest that dietary diversity was perceived as something all people, both rich and poor, could achieve. There was significant overlap between local and scientific understandings of dietary diversity, suggesting that novel information on the importance of dietary diversity promoted through education will likely be easily integrated into the existing knowledge systems.